2018
DOI: 10.1007/s00484-018-1536-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of geographical and climatic properties on grass pollen and Phl p 5 allergen release

Abstract: The Poaceae family, including grasses, comprises several cosmopolitan and allergenic species. The aim of this study was to determine the correlations between Poaceae pollen and Phl p 5 allergen concentrations in two cities with different geographical and climatic properties in Turkey. Pollen were collected from Burkard traps in Ankara and Zonguldak. Phl p 5 sampling was carried out between March and October in both 2015 and 2016 using a BGI900 Cascade High Volume Air Sampler (900 L/min.). The concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Due to high atmospheric humidity, Poaceae pollen grains with a delicate and thin pollen wall ( Buters et al., 2015 ) can be easily burst and release free fraction of allergenic molecules in ambient air ( D'Amato et al., 2010 ). By contrast, we observed, similarly to Alan et al. (2018) that airborne Phl p 5 allergen concentrations significantly decreased with increasing relative air humidity, presumably as a result of increased sedimentation velocity of humid pollen allergens.…”
Section: Discussionsupporting
confidence: 75%
“…Due to high atmospheric humidity, Poaceae pollen grains with a delicate and thin pollen wall ( Buters et al., 2015 ) can be easily burst and release free fraction of allergenic molecules in ambient air ( D'Amato et al., 2010 ). By contrast, we observed, similarly to Alan et al. (2018) that airborne Phl p 5 allergen concentrations significantly decreased with increasing relative air humidity, presumably as a result of increased sedimentation velocity of humid pollen allergens.…”
Section: Discussionsupporting
confidence: 75%
“…It can be seen that the air masses were bordered with the hills which lays in parallel to Black Sea. Because similar result was already obtained with Poaceae pollen, this could be characteristic of cities on Black Sea coastal line [7]. It was reported that Artemisia pollen concentration in Zonguldak atmosphere was 33, 36, 36 pollen/m 3 respectively during 2007-2009 [8].…”
Section: Resultssupporting
confidence: 77%
“…Kozlu is a district with garden houses. Although significant difference was observed between pollen and allergen concentration in one aerobiological station [7], such a difference was not observed in pollen concentrations between stations. This can be interpreted that pollen and allergens have different aerodynamic.…”
Section: Resultsmentioning
confidence: 59%
“…The geographical properties of place in which aerobiological station is placed is also important for collecting airborne especially transported pollen. It was shown that Zonguldak city center is protected from pollen and allergen transported from the south of Zonguldak by hills that lay behind Zonguldak [7]. Therefore, data of two aerobiological stations in Zonguldak were compared using different statistical approach in this study, in order to demonstrate of effect of elevation changes.…”
Section: Introductionmentioning
confidence: 99%